Cyclic codes of prime power length from generalized cyclotomic classes of order 2r. Issue 4 (19th May 2018) - Pankaj,; Pruthi, Manju
Abstract: In this paper, we first introduce generalized cyclotomic classes of order 2 r, r  ≥ 1 and then present a special class of cyclic codes with length p m . We also obtain lower bound on the minimum odd weight of these codes.